HOW MUCH DO CANADIAN SOCIAL WORKERS KNOW ABOUT PREMENSTRUAL SYNDROME AND PREMENSTRUAL DYSPHORIC DISORDER, AND DOES THIS AFFECT THEIR ASSESSMENT OF MOTHERS? - Barry, Lynn; Tutty, Leslie (Canadian Social Work Review / Revue canadienne de service social)

(untitled) (Canadian Association for Social Work Education / Association canadienne pour la formation en travail social (CASWE-ACFTS), 2023)
PMS and PMDD symptoms interfere in some women’s daily coping abilities, including their mothering. Social workers assess mothering ability but may not understand the negative effects of PMS/PMDD. This study examines social workers’ knowledge about PMS/PMDD and whether this influences their assessments with mothers, surveying 521 Canadian social workers. The Premenstrual Experience Knowledge Questionnaire (PEKQ) assesses the biopsychosocial aspects of premenstrual knowledge. Social workers scored an average of 60.5%. They were least knowledgeable about SSRI treatments, suicide rates, and symptoms. Higher scores were associated with having one’s own premenstrual symptoms and PMS symptoms that interfered more in one’s life. Only 5.1% of social workers addressed PMS/PMDD in their mothering assessments, with significant relationships between PMS/PMDD inquiry and worker age, knowledge scores, training, and personal premenstrual symptoms. These results can educate social workers, raising awareness of the possible negative impacts of PMS/PMDD on mothering, which could lead to changing their assessment practices and identifying these treatable conditions. This awareness-raising is especially critical when PMDD/PMS affects mothering to the degree that children’s safety might be compromised.